Responding to the opioid and overdose crisis with innovative services: The recovery community center office-based opioid treatment (RCC-OBOT) model. (November 2019) - Ashford, Robert D.; Brown, Austin M.; McDaniel, Jessica; Neasbitt, Jenna; Sobora, Chad; Riley, Robert; Weinstein, Lesley; Laxton, Aaron; Kunzelman, Justin; Kampman, Kyle; Curtis, Brenda
Abstract: Opioid use disorder (OUD) and opioid-related overdose mortality are major public health concerns in the United States. Recently, several community-based and professional innovations - including hybrid recovery community organizations, peer-based emergency department warm handoff programs, emergency department buprenorphine induction, and low-threshold OUD treatment programs - have emerged or expanded in an effort to address significant obstacles to providing patients the care needed for OUD and to reduce the risk of overdose. Additional innovations are needed to address the crisis. Building upon the foundational frameworks of each of these recent innovations, a new model of OUD pharmacotherapy is proposed and discussed: the Recovery Community Center Office-Based Opioid Treatment model. Additionally, two potential implementation scenarios, the overdose and non-overdose event protocols, are detailed for communities, peers, and practitioners interested in implementing the model. Potential barriers to implementation of the model include service reimbursement, licensing regulations, and organizational concerns. Future research should seek to validate the model and to identify actual implementation and sustainability barriers and best practices. Highlights: RCC-OBOT model developed in partnership with medical, clinical, & community-based partners. The model combines novel innovations that show efficacy in responding to the opioid crisis. Engaging higher-risk individuals in the community may improve retention and outcomes.